Hack/slash, volume 5 ebook - Seeley, Tim (Hack/Slash (2021), 2025)
When Cassie discovers a potential cure for slashers, she accidentally kickstarts a chain of events that will lead to the ultimate betrayal at the hands of a man she thought she could trust! Giant monsters, Vlad's man-eating family, the secret life of Cat Curio, and the final showdown fans have waited years to see!This HACK/SLASH DELUXE EDITION collects MERCY SPARKS: A SLICE OF HELL and issues #12-25 of the ongoing Image Comics series, including guest stories by writers JUSTIN JORDAN (LUTHER STRODE), STEVE SEELEY and MICHAEL MORECI (Barbaric). Also includes a brand-new bonus story by acclaimed creators STEVE ORLANDO and STEVE KURTH!